Study of substructure analysis of supercluster S [227+006+0078] radial velocity range of 21300 km/s to 23400 km/s - Malla, Janak Ratna; Saurer, Walter; Aryal, Binil (Scientific World, 2022)
This paper presents the search for substructures within the Supercluster S [227+006+0078]. To use the spectroscopic database (7th data release) of galaxies, studied the number density, all-sky distribution, and redshift maps to identify substructures based on their richness and compactness. And also to find out the substructures within the Supercluster, using the contour plot of number densities of galaxies within the appropriate radius values and number of nearby galaxies.